Comparative analysis of toxicity of treatment protocols ALL-BFM-95m and ALL-MB-2008 for acute lymphoblastic leukemia in children in Uzbekistan (Eurasian Scientific Herald, 2022)
Over the past two decades, significant progress in the treatment of children with acute lymphoblastic leukemia has been made in many countries, also in low- and middleincome countries (LMICs), but survival rates remain significantly lower than in developed countries [2,5,6]. Inadequate Accompanying therapy and the resulting high mortality from toxicity are important reasons for treatment failure in children with acute lymphoblastic leukemia in LMICs